Response to: Comment on “The evaluation of nailfold capillaroscopy pattern in patients with fibromyalgia’’ - İlke Coşkun Benlidayı and Esra Kayacan Erdoğan and Aylin Sarıyıldız (Archives of Rheumatology, 2021)
We deeply thank to Dr. Lambova for her appreciable point of view and comments on our recent article entitled “The Evaluation of Nailfold Capillaroscopy Pattern in Patients With Fibromyalgia”. The results of our study revealed a significantly higher mean capillary loop diameter, higher number of avascular areas, micro-aneurysms, and neoangiogenic capillaries in patients with fibromyalgia, compared to healthy controls.[1] On the other hand, none of the patients reported symptoms of Raynaud’s phenomenon. However, patients with certain findings in capillaroscopy could be candidates of future Raynaud’s phenomenon/disease. It is well-accepted that abnormal capillaroscopic findings such as micro-aneurysms, avascular areas, and neoangiogenic capillaries are not expected in primary Raynaud’s phenomenon, that is to say, Raynaud’s disease. Nevertheless, primary Raynaud’s phenomenon may transit to secondary Raynaud’s phenomenon, and an abnormal nailfold capillaroscopy pattern is regarded as the best predictor of this transition.[2,3] In a prospective study by Hirschl et al.,[4] the annual incidence of transition to suspected secondary Raynaud’s phenomenon and secondary Raynaud’s phenomenon was found to be 2% and 1%, respectively. On a different point of view, concomitant fibromyalgia is a frequent comorbidity in patients with autoimmune and inflammatory rheumatic diseases.[5,6] In this regard, it is also likely that these patients, particularly those with abnormal capillaroscopic findings, present with signs/ symptoms of autoimmune and inflammatory rheumatic diseases in the future. Generalized pain may be the early symptom of an autoimmune inflammatory rheumatic disease among this particular subgroup of patients. In the light of this hypothesis, it is of worthy to follow the patients with abnormal capillaroscopic findings for autoimmune inflammatory rheumatic diseases. Abnormal capillaroscopic findings among a certain number of patients with fibromyalgia may be related to the potential role of inflammation in fibromyalgia etiopathogenesis.[7] Further research would be of value to clarify this hypothetic consideration. Moreover, the findings of our study highlight the need for observing these patients for the development of possible primary or secondary Raynaud phenomenon. In this regard, regular clinical observation of these individuals, along with laboratory examination when necessary, would be of paramount importance.